IMPLEMENTATION OF THE BEST EMPLOYEES SELECTION IN WANAPOTENSI GUNA (WPG) COMPANIES USING TOPSIS METHOD BASED ON WEBSITE - Suseno, Beka; -, Suyanto (Jurnal Sistem Informasi dan Ilmu Komputer, 2022)
The number of employees at PT. Wanapotensi Guna will make it difficult for companies to find the best employees, the aim is to improve employee performance to be better every year, the best employee selection is held. The problem that occurs in the process of selecting the best employees so far is that data processing is still manual so it takes a long time. Based on the problems above, the researcher provides a solution to make a decision support system for selecting the best employees using the Topsis method and the Waterfall development method and the programming language used is PHP. Results with DSS for selecting the best employees at PT. Wanapotensi Guna can also minimize the risk of losing employee data, making selection evaluation criteria. the best employees according to predetermined criteria,   Keywords :SPK,Best Employee, Topsis, Waterfall .Php.